The impact of pricing, lead time and capacity policies in a two-echelon supply chain. Issue 1 (2018) - Apornak, Arash
Lead-time, price and capacity are common strategies used in supply chains facing uncertain or variable demand. Each provides a mechanism to absorb the uncertainty. In some supply chains, products must be produced before demand is realised. This typically is caused in situations where production takes a long time and the selling period is short, fashion goods for instance. In this paper we assume a two-echelon supply chain consisting of a supplier and a retailer facing price and lead time sensitive demand. The decision process is modelled by Nash equilibrium and Stackelberg game. The equilibrium strategy of these two players is obtained by investigating the impact of variable decisions on the players' profit then compares the performance of the corresponding chain and capacity decision according to historical data as a benchmark. The results illustrated that the profit of supplier and retailer is more Nash equilibrium compared with Stackelberg game.